2013
DOI: 10.1155/2013/345968
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Common Carotid Artery Segmentation Based on Active Shape Model

Abstract: Carotid atherosclerosis is a major reason of stroke, a leading cause of death and disability. In this paper, a segmentation method based on Active Shape Model (ASM) is developed and evaluated to outline common carotid artery (CCA) for carotid atherosclerosis computer-aided evaluation and diagnosis. The proposed method is used to segment both media-adventitia-boundary (MAB) and lumen-intima-boundary (LIB) on transverse views slices from three-dimensional ultrasound (3D US) images. The data set consists of sixty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…Yang et al [10] proposed a method for common carotid artery segmentation based on the Active Shape Model. They reported that the method they used for their dataset yielded a DICE of 94.4% for the MA contours and 92.8% for the LI contours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al [10] proposed a method for common carotid artery segmentation based on the Active Shape Model. They reported that the method they used for their dataset yielded a DICE of 94.4% for the MA contours and 92.8% for the LI contours.…”
Section: Resultsmentioning
confidence: 99%
“…Several automatic or semi-automatic methods for detecting the contours of the carotid arteries from ultrasound images in the transversal view have been proposed [8]- [10]. Due to its robustness to noise and boundary gaps, the active contour model (ACM), which is also called "snakes," proposed by Kass et al [11], is being widely used for contour detection in medical images.…”
Section: Introductionmentioning
confidence: 99%
“…However, we have found that some authors pointed out the need for automated measurement of carotid lumen diameter [47][48][49]. The lumen segmentation algorithms have been classified into regional-based vs. boundary-based: region-based [17,18], boundary-based [19][20][21][22]. Here, we describe each of these techniques and their limitations and discuss how they validated the measured parameters.…”
Section: Brief Survey and Benchmarkingmentioning
confidence: 99%
“…We have classified these techniques into three categories [10,15,16] as: region-based [17,18], boundary-based [19][20][21][22] or fusion-based [6].…”
Section: Introductionmentioning
confidence: 99%
“…They claimed that their method has achieved 100% accuracy in a group of 38 healthy subjects. Xin Yang et al [3] proposed to using Active Shape Model (ASM) to segment both media-adventitia-boundary (MAB) and lumen-intima-boundary (LIB) on transverse view slices from 3D ultrasound images. They used 340 two-dimensional CCA baseline contours in ASM offline training phase and another 340 two-dimensional CCA images in ASM online But it suffers from the fact that it needs a lot of time for training the model and it is very sensitive to the initial position.…”
Section: Introductionmentioning
confidence: 99%